ANALISIS KINERJA KEUANGAN MENGGUNAKAN PENDEKATAN PEARLS PADA KOPERASI SIMPAN PINJAM MADANI NUSA TENGGARA BARAT - I NENGAH ARSANA; I MADE SUARDANA; NI NYOMAN YULIATI; AGUS KHAZIN FAUZI (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this research is to find out the complete picture financial performance of KSP Madani NTB. The type of data used is quantitative data, while the source of the data in this study comes from secondary data, which is obtained financial reports from KSP.Madani NTB, such as balance reports, SHU calculation reports, and loan reports that are problematic. The analysis technique used is the PEARLS analysis approach. The results of this study indicate that the financial performance of KSP. Madani NTB in terms of (1) The protection component (P) shows ideal financial performance, (2) The effective financial structure (E) component, generally indicate ideal financial performance, while what is in the less ideal category is the ratio of net loans to total assets (E1), the ratio of assets invested in long-term investments (E3), and the ratio of assets funded by members' savings in the form of savings and time deposits (E5), (3) The asset quality component (A) shows less than ideal financial performance, ( 4) The components of rates of return and costs (R), generally indicate ideal financial performance, only the ratio of net income to total assets (R12) is in the less than ideal category, (5) The liquidity component (L) shows ideal financial performance, ( 6) The sign of growth (S) component shows less than ideal financial performance